Universal health coverage in Pakistan: exploring the landscape of the health system, health seeking behaviours, and utilization of health services - Babar Tasneem Shaikh (Elsevier, 2024)
Summary: The attainment of the noble objective of Universal Health Coverage (UHC)- 'leaving no one behind' necessitates sufficient financial resources, an ample supply of skilled healthcare professionals, and the availability of essential services as part of a basic package This paper presents an analysis of the health system, health seeking behaviours and health service utilization en route to UHC in Pakistan. We have used the UHC 14 tracer indicators of service coverage to see where Pakistan stands, what are the gaps and what needs to be done. Pakistan clearly is lagging behind its neighboring countries. The country's health system ought to work on health seeking behaviours and broader determinants of health. The pursuit of UHC demands a shared responsibility and collective action, with stakeholders from different sectors uniting their efforts and expertise. Together, they can establish robust systems, design comprehensive policies, allocate adequate resources, and implement interventions that transcend disciplinary boundaries.